After the crash : financial crises and regulatory responses - O'Halloran, Sharyn 1963- Herausgeber; Groll, Thomas, 1982- 1982- Herausgeber (Columbia University Press, 2019)
"The 2008 financial crash was the worst financial crisis and the most severe economic downturn since the Great Depression. It triggered a complete overhaul of the global regulatory environment, ushering in a stream of new rules and laws to combat the perceived weakness of the financial system. While the global economy came back from the brink, the continuing effects of the crisis include increasing economic inequality and political polarization. Ten Years After the Crash is an innovative analysis of the crisis and its ongoing influence on the global regulatory, financial, and political landscape, with timely discussions of the key issues for our economic future. It brings together a range of expert and practitioner perspectives, including the Nobel Prize winner Joseph Stiglitz, the former congressman Barney Frank, the former treasury secretary Jacob Lew, the former deputy governor of the Bank of England Paul Tucker, and Steve Cutler, general counsel of JP Morgan Chase during the financial crisis. Each poses crucial questions: What were the origins of the crisis? How effective were international and domestic regulatory responses? Have we addressed the roots of the crisis through reform and regulation? Are our financial systems and the global economy better able to withstand another crash? Ten Years After the Crash is vital reading as both a retrospective on the last crisis and analysis of possible sources of the next one"--